Ritual and religion in the making of humanity - Rappaport, Roy A. (Cambridge studies in social and cultural anthropology, 1999)
Roy Rappaport argues that religion is central to the continuing evolution of life, although it has been displaced from its original position of intellectual authority by the rise of modern science.